MICROTOPONYMS OF ANTHROPOGENIC ORIGIN OF THE VILLAGE OF VELYKI DIDUSHYCHI (Stryi district, Lviv oblast) - SEHIN, Liubomyr (Linguistic and Conceptual Worldviews, 2023)
The author analyzes the lexical-semantic features of microtoponyms of anthropogenic origin in the village of Velyki Didushychi (Stryi District, Lviv Oblast). As a result of the study of 287 microtoponyms it was found that man-made objects constitute a significant part, and 11 semantic groups of microtoponyms were distinguished: the names for trades, methods of household management, types of settlements, residential, cultural, economic and household buildings, which indicate the method of land development, on a part of the whole, on the border of land allotments, on the purpose and use of the area, on the roads of communication, on the social status of the owner, as well as in which the beliefs of the inhabitants and the formation of ethnonyms are expressed. In each thematic group, the meaning of motivational bases is distinguished, and their etymology is clarified. On the basis of calculations, it was highlighted that the most significant part in the analyzed onomasticon involves the stems for the definition of residential, cultural, economic and household buildings, which became the basis for the creation of 43 proper names of a monolexical, compound and prepositional structure, which is related to ensuring the livelihood of people. Within these groups, the largest number of names was recorded from the appellatives tserkva [church] / doroha [road] and lenia - 5 and 9 nominations, respectively. It was outlined that th propriatives for determining trades, methods of household management are also productive, as well as those that indicate the purpose and use of the area and that reflect the beliefs of the inhabitants - from 10 to 17 units. Thematic groups that are unproductive in the studied territory are outlined, among which microtoponyms formed from ethnonyms and which indicate the social status of the owner are the least represented.